Peripartum Cardiomyopathy: A Case Series - Salim, Md Abu; Rahman, Mohammad Walidur; Adhikary, Dipal Krishna; Arzu, Jahanara; Hoque, Md Harisul; Joarder, Ariful Islam; Mahmood, Manzoor (University Heart Journal, 2020)
Peripartum cardiomyopathy (PPCM) is a life threatening entity of peripartum period characterized by left ventricular systolic dysfunction and heart failure in absence of any known cardiac disease. Though its incidence is rising but there is still uncertainty regarding its incidence, pathogenesis, and optimum management protocol. Retrospective analysis of twenty cases of PPCM admitted, within July 20016 to June 2018 in the department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka is done here. Mean age of study population was 25 (6.3). Majority of the patients were multi-paras 12 (60%). 80% of the patients were diagnosed after delivery. Breathlessness was the most common symptom. Bibasal lung base crepitations was most frequent sign, which was found in 95% cases. Sinus tachycardia was most frequent electrocardiographic change which was found in 80% cases. Mean left ventricular ejection fraction (LVEF) was 35.2(2.8). All the patients had different extent of global hypokinesia of left ventricle (LV) at rest. The patients were treated with bed rest, water and salt restriction, loop diuretic, digitalis, selective Beta-blocker, vitamin B complex and an anticoagulant in relevant cases in antepartum period, Angiotensin converting enzyme inhibitor (ACEI) or Angiotensin receptor blocker (ARB) was added in postpartum period.70% patients were clinically improved and in 45% the left ventricular functional status returned to normal. 30% developed persistent cardiomyopathy beyond six months of presentation. Maternal mortality was 1 (5%). Among all live births three had intra uterine growth retardation. The pathophysiology, emerging investigations modalities, updated management protocol, and prognosis of PPCM are also discussed in this review. University Heart Journal Vol. 17, No. 1, Jan 2021; 71-75